1H-NMR -based metabolic analysis on biocompatibility of dental biomaterials. (March 2022) - Zhou, Jinglin; Ning, Ke; Yang, Yi; Zou, Ling; Xue, Jing; Kong, Xiangli; Li, Wei
Highlights: Metabolomic method could demonstrate well the difference among 3 dental biomaterials There are 12 influenced metabolic pathway from MC3T3-E1 cultivated related to dental biomaterials Aerobic oxidation pathway, the metabolism of amino acids and lipid could correlate with the biocompatibility of different materials. Abstract: Researches on the biocompatibility of dental biomaterials has become a hotspot. As a new subject, metabolomics has unique advantages in research of material compatibility. This paper aims to utilize 1 H-NMR method to analyze and evaluate the biocompatibility of 3 common dental biomaterials (Titanium, Hydroxyapatite-calcium phosphate bioceramics and Poly-methyl-methacrylate). We utilize 1 H-NMR method to analyze extracellular small molecular metabolites of MC3T3-E1 osteoblasts cultivated on 3 dental biomaterials above. Metabolite path is visualized using metPA network software to identify different characteristic metabolites, with the same software biocompatibility of these materials is also evaluated. The metabolic profiles of the 3 experimental groups are clearly distinguished from the control group. 25 characteristic metabolites are identified that could distinguish the metabolic profiles from experimental groups, many of which are mapped to pathway processes. Amino acid metabolism, glucose metabolism, and Lipid metabolism are correlated with the biocompatibility of these materials. Conclusions: 1 H-NMR method is a method to analyze and evaluate the biocompatibility of dental biomaterials.